Multilevel modeling of the impact of bullying on Indonesian students' mathematics achievement based on PISA 2022 Data - Sukowati, Diah; Kismiantini, Kismiantini (Universitas Islam Negeri Raden Intan Lampung, 2025)
Bullying in schools negatively affects students' psychological well-being and academic performance. Despite anti-bullying policies, bullying remains prevalent in Indonesia, impacting students' mathematics achievement. This study examines the impact of different types of bullying on Indonesian students' mathematics achievement using Program for International Student Assessment (PISA) 2022 data through a multilevel modeling approach. Multilevel modeling is used to analyze the hierarchical effects of physical, verbal, and relational bullying on students' mathematics scores, considering socioeconomic and school-level factors. Physical bullying significantly lowers mathematics achievement by reducing concentration and motivation. Verbal bullying, however, is linked to higher scores as students strive to prove themselves. Relational bullying has no significant effect. Socioeconomic status and family support positively influence achievement, while school location also plays a role. Schools must strengthen anti-physical bullying programs to mitigate its negative academic impact. This research has implications for understanding the nuanced effects of bullying, which can help policymakers design targeted interventions to foster safer and more supportive learning environments, ultimately improving students' academic outcomes.